Questionário da Dissociação Somatoforme [Somatoform Dissociation Questionnaire] - Espirito-Santo, Helena (2018)
CHARACTERIZATION: SDQ is a 20-item self-response questionnaire that measures the intensity of somatoform dissociation. STRUCTURE AND SCORING: The items are answered with a Likert-type 5-point scale. The range of scores is 20 - 100 (high dissociation). PSICOMETRIC CHARACTERISTICS: Adequate corrected item-total correlations (varying between r = 0.31 and r = 0.63). Internal consistency, measured by Cronbach's alpha was 0.94. CUTOFF SCORE and DIAGNOSTIC ACCURACY: The best sensitivity-specificity relation of the SDQ-20 was established at a cut-off point of 35. The sensitivity rate was 0.73, the specificity rate was 0.66, positive predictive value was 0.54, and negative predictive value was 0.21.